Analysis of stresses in FeSi sheets induced by laser cutting. (December 2018) - Bulin, T; Roupcova, P; Ondrusek, C; Schneeweiss, O.
Abstract: The stresses induced by laser cutting in the non-oriented fully processed electrical FeSi sheets were investigated using X-ray diffraction, Mössbauer spectroscopy, and magnetic measurements. The magnetic measurements were used for studies of changes in magnetic properties due to changes in stresses. The original laser cut samples were compared with those after heat treatment. The magnetic measurements appeared as the most sensitive method among those selected for the present study. The influence of stresses has an impact on the shape of the hysteresis loops and the permeability in dependence on the excitation magnetic field. The selected heat treatment caused decrease of stresses and improvement of magnetic properties of the sheets.